Numerical simulation of near-gravity coal particle behavior in a dense medium cyclone using a mixture model coupled with a discrete phase model. Issue 8 (3rd August 2021) - Aketi, Veera Asha Kumari; Teja Reddy, Vakamalla; Mangadoddy, Narasimha; G Ε, Sreedhar; Raparla, Shiva Kumar; Kumar, Rajan
ABSTRACT: In general, the washing of coal is greatly influenced by the amount of near-gravity material (NGM) present at the desired cut density. It is observed that the presence of a high percentage of NGM coal results in significant misplacement of particles to wrong products and reduces the separation efficiency of dense medium cyclone (DMC). In this work, an attempt is made to study the behavior of different sizes of NGM coal particles at three feed relative densities inside 350 mm DMC using a discrete phase model (DPM) superimposed on the magnetite medium segregation simulated by modified mixture model. The Reynolds stress model (RSM) is used to resolve turbulence. The DPM is adopted to track different sizes and densities of coal particles, and then a partition curve is constructed to calculate the Ecart probable (Ep) error, percent misplacement, and imperfection. The results show that the lighter and heavier density coal particles away from the separation cut density exhibit very short residence times. Fine-sized coal particles close to the cut density have a significant misplacement compared to the coarse-sized particles having the same density. It is also observed that NGM coal particles show very long residence times irrespective of size.